The Influence of Inclusive Education Programs on the Social Development of Children with Special Needs - Nur, Rejeki; Kaya, Cemil; Demir, Ahmet (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Inclusive education has become a fundamental approach to ensuring that children with special needs are integrated into general education settings, promoting social interaction and development alongside their peers. However, there is a lack of sufficient empirical evidence regarding the specific impact of inclusive education programs on the social development of children with special needs. This study explores how inclusive education programs influence the social development of children with special needs, focusing on improvements in social skills, peer relationships, and social integration. A mixed-methods approach was employed, involving 150 students with special needs across five schools that implement inclusive education programs. Data were collected through standardized social skills assessments, teacher reports, and interviews with parents and students. The results indicated that students in inclusive settings demonstrated significant improvements in social skills, particularly in peer interactions and communication. Teachers reported enhanced social integration of these students in classroom activities, and parents noted a positive shift in their children’s ability to engage socially outside of school. The study concludes that inclusive education programs provide critical social development opportunities for children with special needs, fostering greater acceptance and interaction with their peers. These findings suggest that inclusive education should be further promoted as a vital approach for enhancing social